The Effect of Income Uncertainty and Time Pressure on Work-Related Stress Among Gojek Drivers in Bandung - Ariq Vero Ariyanto; Didin Kristinawati (Cakrawala Repositori IMWI)
The rapid growth of the digital economy has driven a significant increase in gig workers, including online transportation drivers who experience precarious working conditions characterized by income uncertainty and high time pressure. This research aimed to analyze the effects of income uncertainty and time pressure on work-related stress among Gojek drivers in Bandung. This study employed a quantitative approach with an explanatory research design. The research sample consisted of 140 Gojek drivers in Bandung City selected using an accidental sampling technique. Primary data were collected through a five-point Likert-scale questionnaire, while secondary data were obtained from company reports, official publications, and previous studies. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS. The results indicated that all measurement indicators met the required validity and reliability criteria. Income uncertainty had a positive and significant effect on work-related stress, with a path coefficient of 0.424, a t-statistic of 6.206, and a p-value of 0.000. Time pressure also had a positive and significant effect on work-related stress, with a path coefficient of 0.335, a t-statistic of 4.363, and a p-value of 0.000. Simultaneously, income uncertainty and time pressure explained 36.8% of the variance in work-related stress. These findings indicate that income instability and occupational pressure are significant factors contributing to increased work-related stress among Gojek drivers. This research implies that digital platforms need to consider incentive policies, work system improvements, and measures to protect the psychological well-being of driver-partners.